Pollinator-Mediated Selection on Floral Traits of Primula tibetica Differs Between Sites With Different Soil Water Contents and Among Different Levels of Nutrient Availability - Wu, Yun; Duan, Xuyu; Tong, Zhaoli; Li, Qingjun (Frontiers in Plant Science, 2022)
Abiotic environmental factors are predicted to affect plant traits and the intensity of plant-pollinator interactions. However, knowledge of their potential effects on pollinator-mediated selection on floral traits is still limited. We separately estimated the effects of soil water (two sites with different soil water contents) and N-P-K nutrient availability (different levels of nutrient addition) on pollinator-mediated selection on floral traits of Primula tibetica (an insect-pollinated perennial herbaceous species). Our results demonstrated that floral traits, plant reproductive success and pollinator-mediated selection on floral traits varied between sites with different soil water contents and among different levels of nutrient addition. The strength of pollinator-mediated selection was stronger at the site with low soil water content than at the site with high soil water content, and first decreased and then increased with increasing N-P-K nutrient addition. Our results support the hypothesis that abiotic environmental factors influence the importance of pollinators in shaping floral evolution.